SLC Transporters as Therapeutic Targets: Emerging Opportunities - Lin, Lawrence (Nat Rev Drug Discov, 2015)
Solute carrier (SLC) transporters — a family of more than 300 membrane-bound proteins that facilitate the transport of a wide array of substrates across biological membranes — have important roles in physiological processes ranging from the cellular uptake of nutrients to the absorption of drugs and other xenobiotics. Several classes of marketed drugs target well-known SLC transporters, such as neurotransmitter transporters, and human genetic studies have provided powerful insight into the roles of more-recently characterized SLC transporters in both rare and common diseases, indicating a wealth of new therapeutic opportunities. This Review summarizes knowledge on the roles of SLC transporters in human disease, describes strategies to target such transporters, and highlights current and investigational drugs that modulate SLC transporters, as well as promising drug targets.